2015
DOI: 10.1038/cgt.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

Dual silencing of Bcl-2 and Survivin by HSV-1 vector shows better antitumor efficacy in higher PKR phosphorylation tumor cells in vitro and in vivo

Abstract: RNA interference (RNAi) is a promising tool for cancer therapy, but its delivery strategy is a major challenge for its application. Oncolytic herpes simplex virus type 1 (HSV-1) is not only an effective antitumor drug but also an excellent vector. Herein, RNAi of oncogenes Bcl-2 and Survivin was combined with oncolytic HSV-1 (ICP34.5-/ICP6-/ICP47-/CMV-GM-CSF) and a new vector HSV010-BS was constructed. Transfected cell viability assays and animal experiments revealed that the dual silencing of Bcl-2 and Surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…Hence, we believe that simultaneous delivery of pDCN+IL-10 modulates the opposing functions of DCN, leading to lower elastin gene expression at transcriptional level. These observations, not only illustrate the independent mode of action of the plasmids, but also corroborate previous publications, where co-delivery of therapeutics/biologics was demonstrated to be superior to mono-domain approaches 62 63 64 65 66 67 .…”
Section: Discussionsupporting
confidence: 90%
“…Hence, we believe that simultaneous delivery of pDCN+IL-10 modulates the opposing functions of DCN, leading to lower elastin gene expression at transcriptional level. These observations, not only illustrate the independent mode of action of the plasmids, but also corroborate previous publications, where co-delivery of therapeutics/biologics was demonstrated to be superior to mono-domain approaches 62 63 64 65 66 67 .…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, by in vitro and in vivo assays, we found that the replication-competent oncolytic adenovirus caused E1A-mediated simultaneous downregulation for ErbB2 and ErbB3 proteins, accounting for its enhanced potency. Chen et al [65] and Chang et al [66] have reported that E1A causes downregulation of HSPA5 and HER2/neu expression and is positively associated with tumor metastasis. Taken together with these reports, oAd/shErbB3-mediated ErbB3 downregulation is predicted to cause multimodal anticancer effects, and it could be an interesting combination therapy candidate for ErbB2-targeted therapies to address the ErbB2/ErbB3 heterodimerization-induced drug resistance in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Mortalin-targeting oncolytic adenovirus was also shown to cause apoptosis in MCF7 cells [67]. Dual silencing of Bcl-2 and survivin by an oHSV-1 vector demonstrates antitumor efficacy in cancer cells [65]. Further, there are trials focusing on developing and establishing this platform more effectively by optimizing the structure and format of RNAi [66,68].…”
Section: Discussionmentioning
confidence: 99%
“…During HSV infection (Figure 1), the host cells bind type I IFN through the IFN receptor, activate the JAK-STAT pathway and upregulate protein kinase R (PKR). Then PKR is activated by its ligand, which will cause phosphorylation of the host's translation initiation factor eIF2α, thereby inhibiting HSV replication and host protein synthesis [17]. However, the C-terminal domain of HSV ICP34.5 protein can bind to host phosphatase PP1α and relocate it to eIF2α, leading to dephosphorylation and restoration of mRNA translation [18] [19].…”
Section: Structure and Function Of Icp345 And Latmentioning
confidence: 99%